In silico structural homology modeling and functional characterization of Mycoplasma gallisepticum variable lipoprotein hemagglutin proteins - Mugunthan, Susithra Priyadarshni; Harish, Mani Chandra (Frontiers in Veterinary Science, 2022)
Mycoplasma gallisepticum variable lipoprotein hemagglutin (vlhA) proteins are crucial for immune evasion from the host cells, permitting the persistence and survival of pathogen. Yet the exact molecular mechanism behind the immune evasion function is not clear. In silico physiochemical, domain analysis, sub cellular localization and homology modeling studies have been carried out to predict the structural and functional properties of these proteins. The outcomes of the present study have provided significant preliminary data for understanding immune evasion by vlhA proteins. Here, we have reported the primary, secondary and tertiary structural characteristics and subcellular localization, presence of transmembrane helix and signal peptide and functional characteristics of vlhA proteins from M. gallisepticum Strain R low. The results show variation between the structural and functional components of the proteins, signifying the role and diverse molecular mechanisms in functioning of vlhA proteins in host immune evasion. Moreover the 3D structure predicted in this study will pave a way in understanding the vlhA protein function and its interaction with other molecules to undergo immune evasion. This study forms the basis for future experimental studies progressing our understanding in the molecular mechanisms used by vlhA proteins.